1981
DOI: 10.1007/bf00544595
|View full text |Cite
|
Sign up to set email alerts
|

A pharmacodynamic and pharmacokinetic comparison of pindolol 20 mg retard and a conventional tablet

Abstract: In 10 healthy volunteers the time course of cardiac beta-adrenoceptor blocking activity, plasma levels and cumulative urinary excretion of pindolol were compared during a 4-day course of pindolol 5 mg (Visken) t. d. s., and one tablet of pindolol 20 mg retard (Visken retard) once a day. After oral administration of the 20 mg retard tablet, plasma concentrations of pindolol higher than half the maximum value (1/2 Cp (tmax)) were maintained about 2.5 times as long as after administration of the conventional 5 mg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

1981
1981
2006
2006

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 11 publications
0
6
0
Order By: Relevance
“…Treatments consisted of escitalopram 20 mg + placebo; escitalopram 20 mg + ketanserin 50 mg; escitalopram 20 mg + pindolol 10 mg; and placebo + placebo administered at four different test days separated by a washout period of at least 7 days. Escitalopram, ketanserin and pindolol oral dosages have a C max of 4, 2 and 1 h and a half-life of 27-32, 3-4 and 13-18 h, respectively (Aronson and Delgado 2004;Aellig et al 1981;Hedner et al 1983). An oral dose of 10 mg of pindolol was needed in healthy volunteers to achieve a 37% occupancy of the 5-HT 1a autoreceptor (Rabiner et al 2001).…”
Section: Design and Treatmentmentioning
confidence: 98%
“…Treatments consisted of escitalopram 20 mg + placebo; escitalopram 20 mg + ketanserin 50 mg; escitalopram 20 mg + pindolol 10 mg; and placebo + placebo administered at four different test days separated by a washout period of at least 7 days. Escitalopram, ketanserin and pindolol oral dosages have a C max of 4, 2 and 1 h and a half-life of 27-32, 3-4 and 13-18 h, respectively (Aronson and Delgado 2004;Aellig et al 1981;Hedner et al 1983). An oral dose of 10 mg of pindolol was needed in healthy volunteers to achieve a 37% occupancy of the 5-HT 1a autoreceptor (Rabiner et al 2001).…”
Section: Design and Treatmentmentioning
confidence: 98%
“…16,18,20,42,43) PD and PP are the most potent in b-blockers used in our study and their minimum effective concentrations are in the range of 10-20 ng/ml (human). 18,19,42,43) Systemic plasma concentrations of PD and PP after 90-min iontophoresis were 10Ϯ3 and 5Ϯ1 ng/ml, respectively (Figs. 2B, F).…”
Section: Nsaidsmentioning
confidence: 99%
“…14) Because of their short elimination half-life (from several to less than 6 h), 15) sustained release formulations for oral administration have been developed to prolong the therapeutic effects. [16][17][18][19][20][21] However, the oral absorption of b-blockers is influenced by hepatic first-pass metabolism. 15,22) Thus, the development of transdermal delivery systems may be expected to achieve good maintenance of optimal blood levels and the avoidance of first-pass effects.…”
mentioning
confidence: 99%
“…In one acute study, a rise in supine heart rate was observed (Aellig, 1976). From other studies there has been no evidence for a cumulative effect nor loss of partial agonist activity with chronic dosing (Aellig et al, 1981), nor did cumulative doses of pindolol induce an increase in supine heart rate (Carruthers & Twum-Barima, 1981). The majority of these studies involved the acute administration of pindolol by oral and intravenous routes but as ,3-adrenoceptor blocking drugs are given chronically, it seemed important to compare the effects of a ,8-adrenoceptor blocking drug without partial agonist activity on acute and chronic dosing with a drug with partial agonist activity to see if during chronic administration the 1adrenoceptor blocking effect of the drug would antagonise its own partial agonist activity and as a result have the same effect as a drug without partial agonist activity.…”
Section: Introductionmentioning
confidence: 96%